ANALISIS PENJADWALAN ULANG PADA PERBAIKAN KAPAL KM. USAHA ABADI DENGAN METODE TCTO - Nafa Yunitasari; Fitri Hardiyanti; Arie Indartono (Proceeding Maritime Business Management Conference, 2022)
One means of transportation that has an important role to transport passengers or goods through waters to a certain area is the ship. One of the cargo ship repair processes carried out by PT Adiluhung Saranasegara Indonesia, namely KM Usaha Abadi, where there was a delay due to additional work items. The purpose of this study is to determine the optimal duration and reduce cost overruns by percepting project duration. The methods used are Critical Path Method (CPM) and Time Cost Trade Off (TCTO). The results obtained in the first alternative, namely 1 hour of overtime work from 30 days to 28 days with a total project cost of IDR 1,079,5338,575.4. With the second alternative, 3 hours of overtime work from 30 days to 24 days with a total project cost of Rp1,078,493,823.7. The third alternative is a system of two shifts from 30 days to 18 days with a total project cost of Rp1,097,364,612. With an alternative duration of delay, which is 30 days, the total project cost is Rp. 1,090,425,667,276. So in terms of cost and time, the company should apply the alternative of two shifts.